In Search for the Avian Trigeminal Magnetic Sensor: Distribution of Peripheral and Central Terminals of Ophthalmic Sensory Neurons in the Night-Migratory Eurasian Blackcap (Sylvia atricapilla) - Haase, Katrin; Musielak, Isabelle; Warmuth-Moles, Leonie; Leberecht, Bo; Zolotareva, Anna; Mouritsen, Henrik; Heyers, Dominik (Frontiers in Neuroanatomy, 2022)
In night-migratory songbirds, neurobiological and behavioral evidence suggests the existence of a magnetic sense associated with the ophthalmic branch of the trigeminal nerve (V1), possibly providing magnetic positional information. Curiously, neither the unequivocal existence, structural nature, nor the exact location of any sensory structure has been revealed to date. Here, we used neuronal tract tracing to map both the innervation fields in the upper beak and the detailed trigeminal brainstem terminations of the medial and lateral V1 subbranches in the night-migratory Eurasian Blackcap (Sylvia atricapilla). The medial V1 subbranch takes its course along the ventral part of the upper beak to innervate subepidermal layers and the mucosa of the nasal cavity, while the lateral V1 subbranch runs along dorsolateral levels until the nostrils to innervate mainly the skin of the upper beak. In the trigeminal brainstem, medial V1 terminals innervate both the dorsal part and the ventral, magnetically activated part of the principle sensory trigeminal brainstem nuclei (PrV). In contrast, the lateral V1 subbranch innervates only a small part of the ventral PrV. The spinal sensory trigeminal brainstem nuclei (SpV) receives topographically ordered projections. The medial V1 subbranch mainly innervates rostral and medial parts of SpV, while the lateral V1 subbranch mainly innervates the lateral and caudal parts of SpV. The present findings could provide valuable information for further analysis of the trigeminal magnetic sense of birds.